Theses on Chambliss: Rrughneck and saint - Ferrell, Jeff (Critical criminology, 2016)
In the spring of 1845 Karl Marx sketched a rough intellectual outline for the first chapter of the book The German Ideology (Marx and Engels 1998); unpublished during his lifetime, the eleven epigrammatic statements that made up the outline later came to be known as the "Theses on Feuerbach." Here we use selections from Marx’s "Theses on Feuerbach," with their mix of emergent analysis and eclectic critical vitality, as a template for considering William Chambliss’s scholarly career - a career in which Chambliss’s own models of critical analysis never calcified, but continued to develop with each new project of activist research he took on. Throughout, we argue that Chambliss’s career demonstrates the ways in which critical interpretation intertwines with progressive social engagement, and in so doing exemplifies the eleventh and last of Marx’s theses: "The philosophers have only interpreted the world, in various ways; the point is to change it."